PENGARUH INOVASI ANTENA PADA SIARAN TELEVISI MOBIL - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
The best or optimation of mobile television broadcast will be got some ways, one of this is the antenna’s control of mobile’s te;evision. The additionals require a fairly thorough calculation with look teposition and the distance fron the transmitter. Amplifier of the antenna is called the booster. That is needed voltage enlarge, the input voltage is 12 volt. In this research use the eksternal booster. Transmit power and receive power od antenna inversely proportional distance. With use antenna and booster DXXN 1508 strengening booster is 40-46 x. If in this calculate we use 45 x , input voltage 12 V, the output voltage will be very lage.